The Role of Phenotypic Plasticity and Within‐Environment Trait Variability in the Assembly of the Nectar Microbiome and Plant–Microbe–Animal Interactions - Sergio Quevedo‐Caraballo; Sergio Álvarez‐Pérez (Ecology and Evolution)
ABSTRACT The study of the rules that govern the relationship between phenotypic plasticity, genetic structure, and ecological success has traditionally focused on animals, plants, and a few model microbial species, whereas non‐model microorganisms have received much less attention in this regard. The floral nectar of angiosperms is an ephemeral, island‐like habitat for different highly adapted yeasts and bacteria. The growth of microorganisms in floral nectar depends on their ability to efficiently use the available nutrients and tolerate challenging physicochemical conditions, including high osmotic pressures, unbalanced carbon‐to‐nitrogen ratios, and the presence of diverse defensive compounds of plant origin. The production of alternative phenotypic states in response to environmental cues (i.e., phenotypic plasticity) or independently from these (within‐environment trait variability) might be particularly relevant in floral nectar, in which rapid growth is needed for population persistence and to improve the chance of animal‐mediated dispersal. In this article, we use the nectar microbiome as an example to encourage further research on the causes and ecological consequences of phenotypic plasticity and within‐environment trait variability of microbes. We review previous work on the mechanisms and potential ecological significance of the phenotypic plasticity and within‐environment trait variability displayed by nectar yeasts and bacteria. Additionally, we provide an overview of some topics that require further attention, including potential trade‐offs between different traits that are relevant for adaptation to dynamic nectar environments and the direct and indirect effects of phenotypic variability on the fitness of plants, flower‐visiting animals, and other nectar microbes. We conclude that further research on the causes and ecological consequences of phenotypic plasticity and within‐environment trait variability of microbes is essential to get a better understanding of community assembly and the establishment of ecological interactions in floral nectar and other similar highly dynamic and strongly selective microbial habitats.